Effectiveness of different physical activity programs in improving older adults’ physical capacities: a randomized controlled trial - Cabo, Carolina A.; Hernández-Beltrán, Víctor; Fernandes, Orlando; Mendes, Cláudia; Gamonales, José M.; Espada, Mário C.; Parraca, José A. (Frontiers in Physiology, 2025)
IntroductionAs people age, maintaining physical fitness becomes essential for preserving independence, preventing falls, and improving overall quality of life. Physical activity (PA) mitigates the physical decline associated with aging, enhancing balance, strength, flexibility, and coordination. Effective exercise programs for older people should address age-related physical challenges while remaining safe and accessible.ObjectiveThis study aims to identify the most effective PA program to enhance the physical capacities of older people. By comparing training modalities such as Pilates, Aqua Aerobic, and Sensorimotor training, the study evaluates their impact on key physical abilities to determine the optimal program for promoting functional independence and reducing injury risk in older people.MethodsThis study examined 153 participants, divided into a Control Group (N = 44), Sensorimotor Group (N = 46), Aqua Aerobic Group (N = 41), and Pilates Group (N = 22). Over a 24-week intervention, physical capacities were assessed using the Rikli and Jones battery for strength and flexibility and the timed-up-and-go test for agility and speed. Data were collected pre- and post-intervention. To analyze the changes, we used Student’s T-test and Cohen’s d for effect size (ES), with statistical significance set at p < 0.05. Additionally, ANOVA was applied to examine the main effects of time, group, and their interaction, with Partial Eta Squared used to determine the effect size (ES) in these comparisons.ResultsThe Sensorimotor Group showed significant gains in all tests (p < 0.05), while the Aqua Aerobic Group showed improvements in the Stand and Sit with and without Leaning (p < 0.001), Forearm Flexion (p = 0.005), and Reach Behind your Back (p = 0.002). In contrast, the Control and Pilates Groups did not exhibit significant improvements in any of the assessed variables. The analysis of the moment*group interaction effect revealed significant differences among the groups, except for the Timed Up and Go (TUG) test.ConclusionIn conclusion, sensorimotor and aquatic training significantly improved physical function, especially balance, strength, and mobility, in older people.